Assessing the Life Average Daily Dose (Ladd) due to Heavy Metal Contents in Water Samples from Covenant University, Canaanland, Ota, South West Nigeria (Journal of Informatics and Mathematical Sciences, 2017)
The consumption of water with elevated concentration of lead (Pb) can prevent Hemoglobin Synthesis (Anemia) and results in Kidney diseases. A cross sectional study was conducted in to estimate the risk of exposure to lead via groundwater and bottled water ingestion pathway for the population of Covenant University, Canaanland, Ota, Ogun Sate using Perkin Elmer Optima 8000 ICP-OES. The concentration of Pb, Cr, Cd and As varies from water sample to another with the highest value of .7.07 $μ$gL${}^{-1 }$ was noted in borehole water sample (BH1) behind John Hall. Comparing the value with the International recommended level by USEPA and WHO respectively, 7.07gL${}^{-1}$is less than 15$μ$gL${}^{-1}$ and 10 $μ$gL${}^{-1}$. The Life Average Daily Dose (LADD) estimated in this present study reported higher in BH1 for lead (Pb) and could pose health hazard if accumulated for a long time. This work suggest measures to employ quality water treatment plant to reduce the level of heavy metals in the selected water samples and also more research on radioisotopes in the same water samples.
Keywords: Groundwater; Bottled water; Heavy metals ICP-OES; Chronic daily intake and hazard